Improving the Quality of Education Management, Education Personnel, and Educators in Social Studies Subjects - Rais, Syafruddin; Riyadi, Iswan; Tukiyo, Tukiyo; Sodikin, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study examines the improvement of the quality of education management, education personnel, and social studies subject educators. The study focuses on improving the quality of education management, educators, and education personnel, specifically in social studies subjects. The method used in this research is Library Research. The research stages include 1) Data collection, which is carried out by collecting written data from books, journals, and articles relevant to the model being analyzed, and 2) Data analysis, namely content analysis, where data obtained from literary reading materials is analyzed in depth. The result of this research is that improving the quality of Management is needed to improve the quality of educators in social studies subjects and education staff so that implementing activities in an educational institution runs optimally, effectively, and efficiently. Compared to the preceding years, the Management of educators and education workers at the school or institution that was visited has started showing signs of improvement in their overall performance. The use of certification and the supply of benefits as a mechanism to increase educator welfare is beginning to function even though there are still specific inadequacies in the system.